2013
DOI: 10.1038/ncb2806
|View full text |Cite
|
Sign up to set email alerts
|

Wg and Wnt4 provide long-range directional input to planar cell polarity orientation in Drosophila

Abstract: Planar cell polarity (PCP) is cellular polarity within the plane of an epithelial tissue or organ. PCP is established through interactions of the core Frizzled(Fz)/PCP factors and although their molecular interactions are beginning to be understood, the upstream input providing directional bias/polarity axis remains unknown. Among core PCP genes, Fz is unique as it regulates PCP both cell-autonomously and non-autonomously, with the extra-cellular domain of Fz acting as a ligand for Van-Gogh (Vang). We demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
214
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 154 publications
(219 citation statements)
references
References 64 publications
(92 reference statements)
3
214
1
Order By: Relevance
“…However, this upstream-downstream relationship between the global and core PCP modules has been questioned and alternative model has been proposed in which the two cassettes function in parallel with some cross talk between them [58,59]. Recently, Wu et al showed that an early instructive PCP signal is provided by the two Drosophila Wnt members, Wingless (Wg) and Wnt4, which are expressed in a gradient and act redundantly as Fz ligands [48]. Wg/Wnt4 -Fz binding regulates Fz activity, which, in turn, provides the planar directional cue and triggers asymmetric relocalization of PCP protein complexes.…”
Section: Pcp Functions In Drosophilamentioning
confidence: 99%
See 2 more Smart Citations
“…However, this upstream-downstream relationship between the global and core PCP modules has been questioned and alternative model has been proposed in which the two cassettes function in parallel with some cross talk between them [58,59]. Recently, Wu et al showed that an early instructive PCP signal is provided by the two Drosophila Wnt members, Wingless (Wg) and Wnt4, which are expressed in a gradient and act redundantly as Fz ligands [48]. Wg/Wnt4 -Fz binding regulates Fz activity, which, in turn, provides the planar directional cue and triggers asymmetric relocalization of PCP protein complexes.…”
Section: Pcp Functions In Drosophilamentioning
confidence: 99%
“…The asymmetry is sustained by inter-and intracellular mechanisms that collectively generate a negative feedback loop that enhances and sustains asymmetric PCP protein distribution [61,65,66]. Wu et al showed that Fz (which is localized at the distal part of one cell) binds to an extracellular loop of Vang localized at the proximal side of a neighboring cell; stability of the Fz-Vang intercellular interaction depends on Wg/Wnt4 concentration [48]. The Fz-Vang extracellular binding leads to stabilization of both Vang/Pk and Fz/Dvl complexes to the opposite cellular domains [66].…”
Section: Pcp Functions In Drosophilamentioning
confidence: 99%
See 1 more Smart Citation
“…It should also be noted that the core PCP pathway is often referred to as the non-canonical Wnt/PCP pathway, because it involves Fz receptors and Dvl homologs in a β-catenin-independent signaling pathway. Although the role of Wnts in Drosophila planar polarity is debated (Chen et al, 2008;Wu et al, 2013), Wnt ligands are essential as permissive cues for many vertebrate PCP processes including some PCP-dependent cell movements (Heisenberg et al, 2000;Qian et al, 2007), although recent work has identified an instructive role in the establishment of planar polarity in the ectoderm (Chu and Sokol, 2016).…”
Section: The Pcp Pathway In Vertebrate Epitheliamentioning
confidence: 99%
“…A tight regulation of the composition of these complexes on opposite cell membranes, and consequently on adjacent membranes of two neighboring cells, is essential for the polarizing signal to be propagated across several cell diameters (Adler et al, 2000). Recent studies also implicate Wg and Wnt4 in providing long-range directional input in the Drosophila wing (Wu et al, 2013). Zebrafish embryos carrying mutations in several of the Wnt/PCP pathway core components and in Wnt11/ Wnt5 ligands exhibit a characteristic morphogenetic phenotype, with shorter AP and broader ML body axes due to impaired C&E movements (Heisenberg et al, 2000;Kilian et al, 2003;Marlow et al, 1998).…”
Section: Introductionmentioning
confidence: 99%